Dismissal of Yassir at Bakti Corporation - Zainudin, Dolhadi; Mhd. Sarif, Suhaimi; Ismail, Yusof; Firmansah, Yayan; Yahya, Rohaziah (IIUM Press, 2025)
This case study examines the dismissal of Yassir, a high-performing and respected employee at Bakti Corporation whose career spanned over two decades. Rooted in a strong foundation of Islamic upbringing and values, Yassir's professional journey was marked by perseverance, compassion, and excellence. His rise to Branch Manager reflected the principles of amanah (trust) and ihsan (excellence), which guided his leadership style. However, allegations of misconduct and inappropriate behavior challenged his legacy, culminating in a Domestic Inquiry (DI) and subsequent dismissal. This case study explores the ethical, legal, and Islamic dimensions of workplace justice, accountability, and organizational responsibility. Through an analysis of the evidence, the decision-making processes, and principles such as ‘adl (justice) and taqwa (God-consciousness), the case study provides insights into the interplay between workplace ethics and Islamic jurisprudence in addressing misconduct while maintaining fairness and dignity for all stakeholders.